No Association Between G1246A Polymorphism in HCRTR2 Gene and Risk of Cluster Headache: Evidence From an Updated Meta-Analysis of Observational Studies - Yang, Jiao; Yu, Si-yi; Yang, Jie; Kong, Jing; Liang, Fan-rong; Lv, Zheng-tao (Frontiers in Genetics, 2020)
Background: The hypocretin receptor 2 (HCRTR2) gene may play a pathological role in cluster headache (CH). However, the conclusions of published reports on the relationship between the G1246A polymorphism (rs2653349) in the HCRTR2 gene and risk of CH remain controversial. This purpose of this article is to comprehensively study the current evidence and assess the association between G1246A polymorphism (rs2653349) in the HCRTR2 gene and risk of CH. Materials and Methods: Four electronic databases—ISI Web of Science, CNKI, PubMed, and EMBASE—were comprehensively searched on August 2020 to find and pinpoint all observational articles related to this study. The association between G1246A polymorphism in the HCRTR2 gene and risk of CH under five different genetic models was evaluated based on the summary odds ratio and corresponding 95 confidence interval (95% CI). Methodological quality was assessed based on the Newcastle–Ottawa Scale (NOS). To assist the analysis, RevMan 5.3 software was used to perform subgroup and sensitivity analyses. Egger's and Begg's tests were then conducted to evaluate and assess publication bias. Finally, a meta-regression was carried out by residual (restricted) maximum likelihood (REML). Results: Eight observation studies containing 3,161 healthy controls and 1,964 patients with CH were identified and to be used for the meta-analysis. With methodological quality NOS assessment, the incorporated studies showed an average score of 6.4 stars. The pooled data didn't support the association between G1246A polymorphism in the HCRTR2 gene and CH vulnerability in the overall population (OR: 0.85, 95% CI 0.69, 1.03; p = 0.10). Subgroup analysis by ethnicity showed no significant association between G1246A and CH in either Caucasians (OR: 0.89, 95% CI 0.77, 1.01; p = 0.08) or Asians (OR: 1.65, 95% CI 0.80, 3.41; p = 0.18). The robustness of the conclusion was tested and confirmed with the leave-one-out sensitivity analysis. Meta-regression analysis showed that chronological order of publication appeared to be significantly associated with the heterogeneity (t = 2.47, p = 0.039; residual I2 = 0%, adjusted R2 = 100%). Conclusion: Our present study showed that the G1246A polymorphism in the HCRTR2 gene did not appear to be an accomplice and associated with CH predisposition among either the Asian or Caucasian population.